Analisis Struktural Zellig Harris dalam Bahasa Arab - Tafiati Tafiati; Revi Oktaviari Putri (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2017)
This paper presents a new analytical model in Arabic linguistictreasures. The analysis in the realm of Arabic syntax tends to bedominated by classical approaches and has not touched moderntheory. To close the gap, the authors propose a structural analysismodel of Zellig Harris in the linguistic literature of structuralism. Theauthors analyze several verses of the Qur'an to parse the structure ofthe verses. Based on the analysis, the authors prove that the ZelligHarris's structural syntactic theory can be applied to Arabic as well.